Atlas of the Echiniscidae (Heterotardigrada) of the World–part I: West Palaearctic Echiniscus species - Gąsiorek, Piotr; Vončina, Katarzyna (Zootaxa, 2023)
Traditionally Eurocentric tardigrade taxonomy has started to dissect endemics from very few truly cosmopolitan or widely distributed species, originally described mostly from the West Palaearctic, in the last decade. Obviously, the most problematic for taxonomic identification are species in large genera containing over 100 species in the case of Tardigrada. In limno-terrestrial heterotardigrades, only Echiniscus C.A.S. Schultze, 1840 fulfils this criterion, being a perfect example of taxonomic inflation. In Echiniscidae, this phenomenon results predominantly from the historical fallacy of attaching more importance to chaetotaxy than to the analysis of dorsal plate sculpturing. In this paper, the first of a series on echiniscids of the World, we review the current state of knowledge on the West Palaearctic Echiniscus species. Echiniscus granulatus (Doyère, 1840) and E. spinulosus (Doyère, 1840) are re-described based on multiple population data. Echiniscus lapponicus Thulin, 1911 and E. militaris Murray, 1911 are provided with the first SEM and molecular data, respectively. Following synonymies are made based on analyses of ample comparative material, type series, and redescriptions: E. blumi schizofilus Bartoš, 1941 syn. nov. and E. trojanus Maucci, 1973 syn. nov. of E. blumi blumi Richters, 1903; E. inocelatus Mihelčič, 1938 syn. nov., E. heterospinosus Maucci, 1954 syn. nov. and E. egnatiae Durante Pasa & Maucci, 1979 syn. nov. of E. granulatus; Echiniscus merokensis suecicus Thulin, 1911 syn. nov., E. columinis Murray, 1911 syn. nov., E. batramiae Iharos, 1936 syn. nov., E. jagodici Mihelčič, 1951 syn. nov. and E. laterospinosus Rudescu, 1964 syn. nov. of E. merokensis merokensis Richters, 1904; E. hexacanthus Maucci, 1973 syn. nov. of E. militaris Murray, 1911; E. carusoi Pilato, 1972 syn. nov. of E. spinulosus; E. osellai Maucci, 1974 syn. nov. of E. trisetosus Cuénot, 1932. Two new nomina dubia are proposed: E. apuanus M. Bertolani, 1946 sp. dub. (and a probable synonymy with E. merokensis suggested) and E. pajstunensis Bartoš, 1941 sp. dub. Two new nomina inquirenda are established: E. marleyi Li, 2007 sp. inq. (another chaetotaxy-based morphotype of the Echiniscus blumi-canadensis complex) and E. punctus McInnes, 1995 sp. inq. (the lack of reliable morphological criteria separating it from E. granulatus). We summarise the morphological, phylogenetic and biogeographic information for the West Palaearctic Echiniscus species, and conclude with a total of 21 valid and identifiable taxa. We predict this number will decrease further with solving the species delimitation issues within the Echiniscus blumi-canadensis complex. Among these 21 taxa, 13 species (62%) are to be found solely in the Western Palaearctic and/or entire Holarctic regions. This augments the many recent findings that tardigrades are typically biogeographically structured and form clearly defined faunae.